2019
DOI: 10.3390/jcm8122036
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Sodium Content and Arterial Hypertension in Obese Adolescents

Abstract: Early-onset obesity is known to culminate in type 2 diabetes, arterial hypertension and subsequent cardiovascular disease. The role of sodium (Na+) homeostasis in this process is incompletely understood, yet correlations between Na+ accumulation and hypertension have been observed in adults. We aimed to investigate these associations in adolescents. A cohort of 32 adolescents (13–17 years), comprising 20 obese patients, of whom 11 were hypertensive, as well as 12 age-matched controls, underwent 23Na-MRI of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…All data were processed and analyzed in Horos by one person. Previous analyses of inter-and intra-operator variability in ROI-based measurements, however, revealed no significant differences between measurements [17,37,42]. Fig.…”
Section: Limitationsmentioning
confidence: 76%
See 1 more Smart Citation
“…All data were processed and analyzed in Horos by one person. Previous analyses of inter-and intra-operator variability in ROI-based measurements, however, revealed no significant differences between measurements [17,37,42]. Fig.…”
Section: Limitationsmentioning
confidence: 76%
“…Along with the sub-jects´ calf, four calibration phantoms containing aqueous solutions of 10, 20, 30 and 40 mmol/L (mM) NaCl were scanned as reference standards [18]. Tissue water content was measured by 1H-MRI, using a fat-saturated inversion-prepared SE sequence (inversion time, TI = 210 ms; TA = 6.27 min; TE = 12 ms; TR = 3000 ms; FA = 90•; 1 average, resolution: 1.5 × 1.5 × 5 mm 3 ), as already conducted by other scientists [19,37].…”
Section: Mri Acquisition Protocol and Data Processingmentioning
confidence: 99%
“…NT-proBNP levels were not normally distributed, therefore log transformed NT-proBNP levels were taken for continuous analysis within the Cox proportional hazards regression models. No methods came into operation to fill-up missing data or adjust the model for the presence of missing values 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Contingency tables were used to compare the relative risk of PCI with first- and newer-generation DES for patients with low and elevated NT-proBNP levels. The SPSS 24.0 (IBM Corp.) was used for all statistical analyses 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Whilst 23 Na MRI methods have been important in numerous attempts to quantify the levels of sodium in human skin non-invasively (13)(14)(15)(16), implementation of this in vivo imaging methodology in the clinical arena has yet to occur. Although elevations in skin sodium concentrations have been reported in patients with CKD and hypertension (17 18), data from such studies were obtained using whole body scanners with reported sodium levels ≤ 30 mM for various pathologies (19)(20)(21). Unfortunately, this threshold is well below that typical of ECF sodium concentration (up to 130 mM ( 22)).…”
Section: Introductionmentioning
confidence: 99%